First cut : a novel - Melinek, Judy; Mitchell, T. J (Melinek, Judy. Dr. Jessie Teska novel, 2020)
For San Francisco<U+2019>s newest medical examiner, Dr. Jessie Teska, it was supposed to be a fresh start. A new job in a new city. A way to escape her own dark past. Instead she faces a chilling discovery when an opioid-overdose case contains hints of something more sinister. Jessie<U+2019>s superiors urge her to close the case, but as more bodies land on her autopsy table, she uncovers a constellation of deaths that point to an elaborate plot involving drug dealers and Bitcoin brokers. Drawing on her real-life experiences as a forensics expert, Judy Melinek teams up with husband T.J. Mitchell to deliver the most exhilarating mystery of the year. Autopsy means “see for yourself,” and Jessie Teska won<U+2019>t stop until she has seen it all<U+2014>even if it means that the next corpse on the table could be her own.